McCune Albright Syndrome: A Case Report - Karki, Subhana Thapa; Jain, Vandana (Journal of Nepal Paediatric Society, 2020)
McCune Albright syndrome (MAS) is a very rare genetic disease characterised by any two of the following three findings: café au lait spots, polyosteotic fibrous dysplasia and endocrine disorders. The clinical presentation of MAS may vary depending on which of the various components of the syndrome predominate. Here, we report one case of MAS presenting with precocious puberty.